Life table and demographic parameters of papaya mealybug, Paracoccus marginatus (hemiptera: pseudococcidae) on Hibiscus rosa-chinensis - Mastoi, Muhammad Ishaque; Adam, Nur Azura; Muhamad Awang, Rita; Abd Ghani, Idris; Ibrahim, Yusof; Ahmed Gilal, Arfan (Publications International, 2014)
The papaya mealybug Paracoccus marginatus is an imperative insect pest because of its invasive and polyphagous nature. Age-specific life and fertility tables of P. marginatus were constructed in laboratory conditions (27±2 °C, 60±5% RH). Survival and fertility characteristics of P. marginatus were observed on basis of provision of unlimited food source (Fresh hibiscus leaves) with pesticide and natural enemy free environment. The highest apparent mortality (20.1%) was observed in the 1st instar nymphs with k-value of .097 indicating the key factor in regulating pest population size. The proportion of female to male was 1.09:1. The values for net reproductive rate (Ro), mean generation time (Tc), intrinsic rate of increase (rc), innate capacity of increase (rm), finite rate of increase (λ), and doubling time were recorded as 43.36 female offsprings per female, 30.73 days, 0.1248/day, 0.1227/day, 1.1329 female offsprings/female and 5.65 days respectively. These results will play vital role in development of reliable and sustainable IPM strategy for the pest.